2012
DOI: 10.1007/s00340-012-4916-x
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence properties and energy transfer process of Sm3+–Eu3+ co-doped molybdate red-emitting phosphors by hydrothermal method

Abstract: Eu 3+ and Sm 3+ co-doped molybdate phosphors have been synthesized via hydrothermal method. The phosphors have the advantages of narrower particle size distribution and regular homogeneous shape. The luminescent properties of the molybdate phosphors were systematically studied. The introduction of Sm 3+ into the red-emitting phosphors can generate a strong excitation line at 405 nm, originating from the 6 H 5/2 → 4 K 11/2 transition of Sm 3+ , significantly extending the excitation region for matching the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…29 Similarly, Eu−DMBDC exhibits emissions peaks at 590, 613, and 691 nm, which arise from the 5 D 0 → 7 F J (J = 1, 2, 4) transitions of Eu 3+ ions. 30 As expected, the mixednode Ln-MOFs (Eu X Tb 1−X −DMBDC) simultaneously show the characteristic emissions of the Tb 3+ and Eu 3+ ions (Figure 2d), which further supports the successful incorporation of both ions in the mixed-node Ln-MOFs. These results also suggest that the H 2 DMBDC is an excellent antenna chromophore for sensitizing both Tb 3+ and Eu 3+ ions through the energy-transfer (ENT) process.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…29 Similarly, Eu−DMBDC exhibits emissions peaks at 590, 613, and 691 nm, which arise from the 5 D 0 → 7 F J (J = 1, 2, 4) transitions of Eu 3+ ions. 30 As expected, the mixednode Ln-MOFs (Eu X Tb 1−X −DMBDC) simultaneously show the characteristic emissions of the Tb 3+ and Eu 3+ ions (Figure 2d), which further supports the successful incorporation of both ions in the mixed-node Ln-MOFs. These results also suggest that the H 2 DMBDC is an excellent antenna chromophore for sensitizing both Tb 3+ and Eu 3+ ions through the energy-transfer (ENT) process.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
“…The emission spectrum of Tb–DMBDC displays four characteristic emission peaks at 494, 547, 585, and 618 nm, which can be assigned to the characteristic transitions 5 D 4 → 7 F 6 , 7 F 5 , 7 F 4 , and 7 F 3 of Tb 3+ , respectively . Similarly, Eu–DMBDC exhibits emissions peaks at 590, 613, and 691 nm, which arise from the 5 D 0 → 7 F J ( J = 1, 2, 4) transitions of Eu 3+ ions . As expected, the mixed-node Ln-MOFs (Eu X Tb 1– X –DMBDC) simultaneously show the characteristic emissions of the Tb 3+ and Eu 3+ ions (Figure d), which further supports the successful incorporation of both ions in the mixed-node Ln-MOFs.…”
Section: Resultssupporting
confidence: 65%
“…The excitation spectra of the phosphors comprise a broad band between 200 nm and 330 nm and narrow excitation peaks between 350 nm and 500 nm. According to the literature , the broad excitation band originated in a charge transfer band (CTB) from oxygen to tungsten or molybdenum. The peaks of the excitation spectra in the range 350–500 nm were caused by the characteristic 4f → 4f transition of the Eu 3+ ion within its 4f 6 configuration, which was assigned to 7 F 0 → 5 D 4 , 7 F 0 → 5 L 7 , 7 F 0 → 5 L 6 , 7 F 0 → 5 D 3 , and 7 F 0 → 5 D 2 , as illustrated in the figure.…”
Section: Resultsmentioning
confidence: 99%
“…3, the introduction of Sm 3+ into the red-emitting phosphors can generate a strong excitation line at 402 nm (monitored at 617 nm of Eu 3+ ) due to the 6 H 5/2 → 4 F 7/2 transition of Sm 3+ , thereby extending the excitation region. [30,31] It is indicated that the absorption energy of Sm 3+ at 402 nm may be transferred to Eu 3+ . With the aim of further confirming the influence of co-doping with Sm 3+ , the emission spectra of CaYAl 3 O 7 : Eu 3+ , Sm 3+ are shown in Fig.…”
Section: Energy Transfer Of Eu/sm-coactivated Cayal 3 O 7 Phosphormentioning
confidence: 99%